Pepes Traditional Culinary Tourism Development Strategy in Walahar Village: Strategi Pengembangan Kawasan Wisata Kuliner Tradisional Pepes di Desa Walahar - Dewantara, Yudhiet Fajar; Susanto, Prayogo; Santika, Santika (Jurnal Ilmiah Hospitality Management, 2024)
Walahar Village, located as an entrance to Pantura and an alternative route to Central Java or Jakarta, holds significant potential for the development of traditional culinary tourism, particularly through its Pepes dishes. The village is also home to the Walahar Dam, a popular tourist destination built by the Dutch, making it an attractive location for both historical and culinary tourism. This paper aims to determine the best strategy to develop Pepes-based culinary tourism in Walahar Village, using SWOT analysis to explore the strengths, weaknesses, opportunities, and threats involved.   The study identifies several key strategies for regional development. These include producing content to promote traditional village food, culinary techniques, and production processes, and encouraging local government involvement in creating signage to guide visitors. Additionally, the creation of an icon connected to Walahar Village’s Pepes culinary heritage, potentially through "Instagrammable" features, is crucial to attract younger tourists who engage with visual content on social media. The research also highlights the importance of leveraging electronic media and the internet, including developing websites and social media platforms to enhance promotion and visibility. By incorporating these strategies, the development of Pepes culinary tourism in Walahar Village can capitalize on its rich cultural heritage and its position as a popular travel route, boosting local tourism and economic growth. The findings suggest a comprehensive approach that combines community involvement, infrastructure improvement, and digital marketing to successfully promote Walahar’s culinary offerings while ensuring sustainable tourism development.